Understanding risk management for intentional supply chain disruptions: risk detection, risk mitigation, and risk recovery - DuHadway, Scott; Carnovale, Steven; Hazen, Benjamin (Annals of operations research, 2019)
Strategies to mitigate supply chain risk tend to treat disruptive events as homogenous, despite having different causes and requiring different risk management strategies. We develop a framework to understand effective risk management strategies by considering whether a disruption was caused by an intentional or inadvertent act and whether the source of the disruption was endogenous or exogenous to the supply chain. Based on exploring evidence from risk management strategies for specific disruptions, we find that risk detection is important for both intentional and inadvertent disruptions, while effective risk management practices differ in terms of risk mitigation (relational versus process based approaches) and risk recovery (restructuring versus resilience). The resultant theory-based framework provides a new theoretical perspective on supply chain disruptions and posits that understanding intent and the source of the disruption is critical for appropriate risk management strategies.